Effects of initial albumen quality and mineral oil-chitosan emulsion coating on internal quality and shelf-life of eggs during room temperature storage - Torrico D.D. (2014)
Effects of mineral oil (MO) and mineral oil-chitosan emulsion (MO:CH=25:75) as coatings on internal quality and shelf-life of eggs were evaluated during 5-week storage at 25°C. Eggs with three different initial albumen qualities [Haugh unit (HU): H=87.8, M=75.6 and L=70.9] were evaluated. As storage time increased, HU and yolk index values decreased whereas weight loss increased. Coating with MO and/or 25:75 MO:CH emulsion could preserve the internal quality for at least 4 more weeks for H-eggs and at least 3 more weeks for M and/or L-eggs, all with weight losses <0.92%. All coated eggs had >70% positive purchase intent, and their colour differences at week 0 could not be detected by naked human eye (ΔE*<3.0, noncoated eggs as reference). Consumers significantly differentiated freshly MO-coated from noncoated eggs on overall surface appearance. This study demonstrated that MO and 25:75 MO:CH emulsion coatings could preserve internal quality and prolong shelf-life of eggs. © 2011 The Authors. International Journal of Food Science and Technology © 2011 Institute of Food Science and Technology.